Impact of Social Capital and Entrepreneurial Orientation On Women Entrepreneurs’ Business Performance in Bogor - Putri, Ananda; Burhanuddin; Etriya, Etriya (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Women entrepreneurship is emerging as a significant catalyst for sustainable development and economic growth in urban and rural areas in Indonesia. Empirical evidence suggests that women entrepreneurs having rich social capital and strong entrepreneurial orientation tend to achieve positive business performance.Purpose: This paper investigates the impact of social capital and entrepreneurial orientation on the business performance of women entrepreneurs in Bogor.Design/methodology/approach: A survey was administered to a sample of 136 women-led enterprises in Bogor. The independent variable of social capital was operationalized as trust, norms, and networking, while entrepreneurial orientation was assessed in terms of innovativeness, proactiveness, and risk-taking. Profitability indicating business performance served as the dependent variable. Partial Least Squares-Structural Equation Modeling (PLS-SEM) analysis was performed to test the hypothesized subsequent relationships between the variables.Findings/result: This paper reveals that social capital significantly enhances entrepreneurial orientation (t-stat = 7.192, p < 0.01), and entrepreneurial orientation positively impacts the business performance of women-led enterprises (t-stat = 4.857, p < 0.01). Furthermore, entrepreneurial orientation mediates the relationship between social capital and business performance, as indicated by a significant indirect effect (t-stat = 3.442, p < 0.01).Conclusion: This paper proves the importance of social capital (namely norms, trust, and networking) and entrepreneurial orientation (including risk-taking, proactiveness, and innovativeness) to enhance the profitability of women-led firms. Enhancing social capital can be encouraged through family support, networks, business community engagement, and stakeholder policies in improving entrepreneurial orientation in women, leading to improved business performance and economic growth in Bogor.Originality/value (State of the art): This paper contributes to a better understanding how business performance of women entrepreneurs is influenced by subsequent relationships of social capital and entrepreneurial orientation, including the mediating role of entrepreneurial orientation. Keywords: business performance, entrepreneurial orientation, social capital, small and medium enterprises, women entrepreneurship